Entrepreneurship Education and Self-Efficacy in Primary Schools - Prayogo, Bagus; Ariska; Ghaida, Septi Sabila (CV. Akademi Merdeka, 2025)
This study aimed to provide empirical evidence on the influence of outdoor learning environments and entrepreneurship education on the entrepreneurial self-efficacy of elementary school students. A quantitative approach was employed, involving 282 students from several elementary schools in Cirebon Regency. Data were collected through a structured questionnaire developed based on validated indicators measuring outdoor learning settings, entrepreneurship education, and students’ entrepreneurial self-efficacy. The data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The results showed that the outdoor learning environment had a significant and positive impact on both entrepreneurship education and students’ entrepreneurial self-efficacy. Furthermore, entrepreneurship education served as a mediating variable that strengthened the relationship between the outdoor learning environment and entrepreneurial self-efficacy. These findings highlighted the importance of contextual and experiential learning beyond the traditional classroom in enhancing entrepreneurship education. Therefore, integrating outdoor learning elements into entrepreneurship curricula is a strategic approach to developing entrepreneurial self-efficacy and competencies from an early stage of education.